The Synthesis and Characterization of Pahae Natural Zeolite-Coal Bottom Ash Adsorbent for Fe and Mn Purifier in Well Water - Susilawati Susilawati; Nurul Syafina Lubis; Khatarina Meldawati Pasaribu (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Zeolite is a porous crystalline mineral alumina silica tetrahydrate that has an open three-dimensional framework structure that has channels and cavities filled with metal ions, while Bottom ash is also known to have high porosity and surface area. Thus, both zeolite and bottom ash can be used as adsorbents. This study aims to make an adsorbent based on Pahae natural zeolite with a mixture of bottom ash from coal as an adsorbent for iron (Fe) and manganese (Mn) metals in well water. Adsorbent made from Natural Zeolite Pahae-Coal Bottom Ash with a size of 200 mesh (74 µm) which has been chemically activated with 1 M NaOH solution, was prepared with various compositions of (100:0)%, (95:5)%, (90:10)%, (85:15)%, (80:20)%, (75:25)% respectively, then mold using a hydraulic press with a load of 6 tons of weight for 10 minutes. The mold samples were then physically activated with temperature variations of 600°C, 700°C, and 800°C for 4 hours, respectively. The addition of coal bottom ash filler is known to increase the porosity of the adsorbent with the composition of (75:25)% with an activated temperature of 800°C by 10%. The results of the AAS test showed that the adsorbent made from Natural Zeolite Pahae-Coal Bottom Ash reduced the content of Fe and Mn metals by 92.37% and 53.49% in well water, respectively.